Development of Hybrid-Based Rotemz Teaching Media in Science Learning to Increase Learning Interest of Elementary School Students - Lutfauziah, Asmaul; Retikasari, Frysca Virnanda; Rahmawati, Dewi; Arum, Dian Famila; Fitriyah, Fifi Khoirul (Universitas Nahdlatul Ulama Surabaya, 2024)
This research aims to develop and evaluate the hybrid-based learning media